Implementation of System and Network Security for an Enterprise: Enhancing Security Measures for Enterprise Networks (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Networks today run mission-critical business services that need protection from both external and internal threats. In this paper we proposed a secure design and implementation of a network and system using Windows environment. The basic reasons we care about information systems security are that some of our information needs to be protected against unauthorized disclosure for legal and competitive reasons all of the information we store and refer to must be protected against accidental or deliberate modification and must be available in a timely fashion. We must also establish and maintain the authenticity (correct attribution) of documents we create, send and receive. Finally, the if poor security practices allow damage to our systems, we may be subject to criminal or civil legal proceedings if our negligence allows third parties to be harmed via our compromised systems, there may be even more severe legal problems. Another issue that is emerging in e-commerce is that good security can finally be seen as part of the market development strategy. Consumers have expressed widespread concerns over privacy and the safety of their data companies with strong security can leverage their investment to increase the pool of willing buyers and to increase their market share. We no longer have to look at security purely as loss avoidance in today’s marketplace good security becomes a competitive advantage that can contribute directly to revenue figures and the bottom line. Reviews of latest product with an application to an enterprise with worldwide branches are given.